A efetividade dos tratamentos não cirúrgicos na neuralgia do trigêmeo - Florêncio, David Sildes Fidelis (2022)
Introduction: Trigeminal neuralgia (TN) is one of the pains that affect one or more branches of the trigeminal nerve. It is characterized as chronic pain, like electric shock, producing an imbalance in the stomatognathic functions of mastication and speech, as well as the impact on quality of life. Objective: To develop an overview of systematic reviews that will synthesize evidence on the effectiveness of non-surgical treatments in trigeminal neuralgia. Method: This dissertation is composed by the Articles of Overview Protocol of Systematic Reviews and the Overview article in its entirety. The protocol was submitted to PROSPERO on October 30, 2021, under registration number CRD42021282682. The electronic databases: PUBMED, EMBASE, Lilacs, COCHRANE, Web of Science, Scopus, were searched, in addition to consulting the gray literature (Google Scholar and Open Gray). There was no restriction on language and publication period. Results: After selection, 10 systematic reviews met the eligibility criteria. Pharmacotherapy, acupuncture, photobiomodulation, TENS, botulinum toxin interventions showed effective pain control. Six reviews did not report grade assessment, three characterized with low evidence and one review with two studies, one with low evidence and the other high, the risk of bias uncertain/high. In the AMSTAR 2 assessment, five reviews were rated critically low, three as low, and two as high. Final considerations: The interventions were effective in controlling pain, but the limitations and risk of bias prevent the reproducibility of the results. More studies with methodological rigor are needed to evaluate the effectiveness of non-surgical treatments in Trigeminal Neuralgia.